PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN - Yanti Murni; Hendri Zet (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This study aims to determine the effect of service quality and product quality on customer satisfaction in UPT.Pengelola Clean Water Management. The type of research is quantitative. The data is processed by computerized using SPSS 18.0 program. Number of UPT subscribers. Clean Water Management of Pariaman City continues to increase, but the increasing number of customers was also directly proportional to the increase in the number of customers who complain. The independent variables are service quality (x1) and product quality (x2). Dependent variable is consumer satisfaction (Y). Population and sample used in this research is consumer of UPT. Clean Water Management Pariaman City as many as 79 people and was in place at the time of the research conducted. Data were collected using questionnaires and interviews. Hypothesis testing using multiple regression analysis, t test, F test and determination. The results show partially Quality of service (0,000) and product quality (0.035) have a significant effect on customer satisfaction and simultaneously also affect with the significance of 0.000. The effect is 44.4%